Mass Divorce Filings Among Government Employees with Employment Agreements: Legal Analysis from Maslahah Mursalah Perspective - Handoko, Handoko; Asman, Asman; Amaluddin, Zainal; Asmak, Asmak (Program Studi Hukum Keluarga Islam, 2026)
This study examines the increasing phenomenon of divorce filings among teachers employed under the Government Employees with Employment Agreements (PPPK) scheme in Blitar Regency. The issue has generated social, moral, and religious concerns, particularly due to work placement policies that often separate spouses and potentially weaken family resilience. Existing studies predominantly focus on administrative and employment aspects of PPPK policies, while limited attention has been given to their implications for family welfare and the objectives of Maqasid al-Shari‘ah. This research employs a qualitative method with a normative-literature approach, analyzing maslahah mursalah in Islamic law, scholarly works, statutory regulations, and relevant media reports. The findings indicate that although divorce is legally permissible in Islam, the growing number of marital dissolutions associated with bureaucratic and placement-related pressures reflects insufficient consideration of public welfare and family protection. From the perspective of maslahah mursalah, public policies should not only pursue administrative efficiency but also safeguard family stability as a fundamental social institution. The study concludes that PPPK placement policies require greater integration of family-oriented considerations and that strengthening family resilience programs is necessary to minimize the risk of household disintegration and promote socially responsible governance.